Delayed diagnosis of acute leukemia in a patient with bone pain and fracture - Oztürkmen, Seda; Akyay, Arzu; Biçakçi, Zafer; Karakoç, Yaman; Arikan, Sefik Murat; Celebi-Tayfur, Asli; Ağladioğlu, Sebahat; Olcay, Lale (The Turkish Journal of Pediatrics, 2010)
In childhood acute lymphoblastic leukemia (ALL), non-hematological manifestations involving the musculoskeletal system can also be encountered. These manifestations may cause a delay in the diagnosis of leukemia. The presented case in this report is a six-year-old boy who developed bone pain and long bone fracture and was diagnosed as ALL after a considerable delay. This case is presented to draw attention to the fact that leukemia must be considered in pediatric patients who present with bone manifestations.